A characterization study on electroencephalographic changes and lateralization of functional brain connectivity in boys with developmental coordination disorder - Song, Yiqi; Li, Zhenpeng; Zhu, Xiaotong; Pei, Guang; Hou, Juanyi; Liu, Shiji; Xie, Yi; Xie, Yongtao (Frontiers in Neurology, 2025)
ObjectiveChildren’s motor development is closely related to the development of their brain functions. Currently, the central neural mechanisms in children with developmental coordination disorder (DCD) are poorly understood. This study investigated the changes of EEG patterns in DCD boys.MethodsIn this study, 15 boys with DCD were screened via the Movement Assessment Battery for Children 2nd Edition (MABC-2), and 15 boys with typical development (TD) at the same age were matched as the control group. The electroencephalographic (EEG) signals of the boys were recorded in the resting state and during the visual motor integration (VMI) task, and the relative power, sample entropy (SampEn), phase lag index (PLI), and lateralization of functional connectivity were analyzed.ResultsIn the resting state, no abnormal changes were found in the relative power of the EEG or SampEn of the DCD boys (p > 0.05), and the PLI of each frequency band in the DCD boys was significantly lower than that in the TD boys (p < 0.001). During the VMI task, the θ power of the DCD boys decreased significantly at the right frontal central border (FC2: p < 0.05), the β power decreased significantly at the right frontal central border (FC2: p < 0.001), and the midline of the parietal region (Pz: p < 0.001), and there was no abnormal change in SampEn. The PLIs of the α, β, and γ frequency bands in DCD boys were significantly lower than those in TD boys (p < 0.001), and the functional connectivity of the β band around the cerebral motor cortex was significantly lateralized right hemispheric acceleration (p < 0.05).ConclusionThe brain functional network connectivity of DCD boys may have developmental defects, and the abnormal changes in brain activation, functional connectivity, and lateralization of functional connectivity during movement may be important brain mechanisms for their poor motor coordination. These findings provide a new perspective for analyzing and evaluating the brain function of DCD children.